Cassava germplasm enhancement at the International Institute of Tropical Agriculture (IITA) - Dixon, Alfred G.O.; Asiedu, Robert; Hahn, S.K. (1992)
Cassava (Manihot spp.) improvement strategies at the International Institute of Tropical Agriculture (IITA) are discussed here in relation to the main constraints, target ecologies and utilization of exotic germplasm. Germplasm generated from IITA populations and from other African or non-African programs was evaluated at locations representative of the target ecologies. Selected clones or families were included in one or more special populations set up for specific objectives, Elite broad-based populations were constituted from some entries of the special populations for specific agroecological zones. Other factors examined were procedures to improve special and broad populations, the use of wild and exotic germplasm, the support required from national agricultural research systems (NARS) and the potential benefits.